Natural History of Type II Autosomal Dominant Osteopetrosis: A Single Center Retrospective Study - Wang, Ziyuan; Li, Xiang; Wang, Ya; Fu, Wenzhen; Liu, Yujuan; Zhang, Zhenlin; Wang, Chun (Frontiers in Endocrinology, 2022)
Background Autosomal dominant osteopetrosis II (ADO II, MIM166600) is a sclerosing bone disorder caused by CLCN7 mutation. The main clinical characteristics include minor trauma-related fracture and hip osteoarthritis, whereas cranial nerve palsy and bone marrow failure rarely develop. Although it is generally believed that ADO II has a relatively benign course, the natural course of the disease in Chinese patients remains unclear. Materials and Methods Thirty-six patients diagnosed with ADO II in Shanghai Jiao Tong University Affiliated Sixth People’s Hospital from 2008 to 2021 were studied retrospectively. Among them, 15 patients were followed for an average of 6.3 years (1-14 years). Results In this study, minor trauma-related fractures of the limb were the most typical clinical manifestations. Visual loss (1/36) and bone marrow failure (2/36), was rare in this study. The condition of ADO II seems to be stable in most patients. There were no correlations between markedly elevated bone mineral density (BMD) and minor trauma-related fractures. In total, 21 diseases causing mutations were detected. Among them, the mutation c.2299C>T (p.Arg767Trp) was the most common (16.67%), and mutation c.937G>A [p.(Glu313Lys)] was associated with severe fractures, haematological defects and cranial palsy. Conclusions Minor trauma-related fracture is the most typical clinical manifestation of ADO II and always occurs in. The mutation c.2299C>T (p.Arg767Trp) is in general a relatively common variant, while the mutation c.937G>A [p.(Glu313Lys)] seems to be associated with severe phenotype. In our study, ADO II seems to remain stable over time.